Assessing Radiological Risks and Natural Radioactivity in Building Materials from Ica, Peru - Díaz, Félix (2023)
The study investigated the radon emission rate and potential radiological hazards of high-uranium-content building materials in The Ica area of Southwestern Peru. We used a creative technique that combined a closed chamber and active monitor, and it was improved by a hermetic sealing method to maintain secular equilibrium well. The results showed radon emission rates as low as below detection limits (BDL) up to 52.3 mBq/kg·h. Our analyses with a 3' x 3' NaI detector found radionuclide concentrations in cement samples by gamma spectrometry. We found a high positive correlation between radium activity concentration and radon exhalation rate. The activity concentrations of 226Ra, 232Th, and 40K differ significantly, with maximum values reaching 60.6, 22.3, and 1074 mBq/kg·h. We consider these results significant for the safety of materials in the Peruvian construction sector. And we also hope that they will provide information to support radiological risk management.